2011
DOI: 10.1103/physrevlett.107.188102
|View full text |Cite
|
Sign up to set email alerts
|

Stress Clamp Experiments on Multicellular Tumor Spheroids

Abstract: The precise role of the microenvironment on tumor growth is poorly understood. Whereas the tumor is in constant competition with the surrounding tissue, little is known about the mechanics of this interaction. Using a novel experimental procedure, we study quantitatively the effect of an applied mechanical stress on the long-term growth of a spheroid cell aggregate. We observe that a stress of 10kPa is sufficient to drastically reduce growth by inhibition of cell proliferation mainly in the core of the spheroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
238
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(253 citation statements)
references
References 21 publications
(23 reference statements)
15
238
0
Order By: Relevance
“…These spherical organoids have the same crypt architecture, with minimal physiological environment, suggesting that the organization of the crypt structure can be understood from purely mechanical principles. Spherical organoids allow for controlled experiments on which one could test these theories, following cells in real time, and exerting pressure on them, similarly to [32], in order to test the effect on growth and stem cell dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These spherical organoids have the same crypt architecture, with minimal physiological environment, suggesting that the organization of the crypt structure can be understood from purely mechanical principles. Spherical organoids allow for controlled experiments on which one could test these theories, following cells in real time, and exerting pressure on them, similarly to [32], in order to test the effect on growth and stem cell dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent experiments on colon carcinoma cells in three dimensions have shown that exerting mechanical pressure on an aggregate lowers its division rate in a significant and predictable way [32]. Therefore, in the following section, we make the additional assumptions that pressurebased growth is sufficient to regulate the first stages of crypt development ðk À k d / ðP À P h ÞÞ and that the regulation of cell division rate is proportional to the fraction of the proliferative compartment which we label…”
Section: Stem Cell Kinetics and Homeostasis Regulationmentioning
confidence: 99%
“…[2,3,4]. It is interesting to notice that compressive stresses of slightly less than 1 kPa applied through a piston were recently found to induce a metastatic phenotype in cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that mechanical stresses directly regulate the growth and death rates of cancer cells. Recently, Montel et al have explored this possibility, investigating the effect of a constant stress applied on cellular spheroids over long time scales by inducing osmotic pressure by a solution of dextran, a biocompatible polymer which is neutral and can not be metabolised by mammalian cells [2,3]. Using a similar method, some of us recently reported that a constant low osmotic pressure (1kPa) affects more strongly the proliferative capability of primary human melanoma cells (IgR39) in comparison to the corresponding metastatic ones (IgR37) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Such signalling is mediated through the presence of boundaries, whose shapes determine the formation of morphogen gradients [3] and the local stress state, which in turn controls cell proliferation [4], differentiation [5] and apoptosis [6,7]. Depending on the physical environment, these boundaries may either be static, as is the case for solid substrates, or they may move as new tissue is formed [8].…”
Section: Introductionmentioning
confidence: 99%